Dengzhan shengmai capsule combined with donepezil hydrochloride in the treatment of Alzheimer's disease: preliminary findings, randomized and controlled clinical trial - Huang,Pan (2021)
SUMMARY OBJECTIVE: To observe the effects of Dengzhan Shengmai capsule combined with donepezil hydrochloride on cognitive function, daily living ability, and safety in patients with Alzheimer's disease. METHODS: A total of 294 patients with Alzheimer’s disease were randomly divided into a treatment group and a control group, 147 cases each group. The control group was given oral donepezil hydrochloride 5 mg once a day, and the treatment group was given oral Dengzhan Shengmai capsule 0.36 g three times a day, based on the control group. RESULTS: At 3 and 6 months of treatment, the ADAS-cog score of the treatment group was 48.69±6.23 and 44.24±5.53; for the control group, 45.48±5.94 and 41.57±5.10. The difference between the two groups is statistically significant (p<0.05). At 3 and 6 months of treatment, the NO level in the treatment group was (46.28±6.68) umol/l, (43.55±7.92) umol/l, and the control group was (42.95±7.92) umol/l, (38.89±5.93) umol/l. The differences between both groups were statistically significant (p<0.05). At 3 and 6 months of treatment, ET levels in the treatment group were (156.08±17.39) ng/l, (144.91±17.60) ng/l, and the control group was (150.48±22.94) ng/l, (135.04±10.08) ng/l. Correlation analysis showed that ADAS-cog score was negatively correlated with NO and ET (p<0.001). CONCLUSIONS: Dengzhan Shengmai capsule combined with donepezil hydrochloride can improve cognitive function and the living capacity of patients with Alzheimer’s disease, reduce the production of neurotoxic substances NO and ET, and provide higher safety.